AB0490 Kaltenborn's Manual Mobilization Method for Pain Relief in RA Hand Joints: Clinical and Ultrasound Findings in a Pilot Study. (9th June 2015) - Levitsky, A.; Kisten, Y.; Nordström, P.; Lind, S.; Vivar, N.; van Vollenhoven, R.F.
Abstract : Background: Pain is an important manifestation of rheumatoid arthritis (RA) and it is imperative to find complementary options for patients experiencing pain despite antirheumatic treatment. Kaltenborn's manual mobilization is a complementary and alternative medicine (CAM) method based on gentle traction and passive motion. It has been tested extensively in osteoarthritic joints and found to provide pain relief, but there are no published studies to date on the use of this method in RA hand joints under ultrasound (Doppler) surveillance. Objectives: The aim of this pilot study was to preliminarily assess the effectiveness of the Kaltenborn manual mobilization method in reducing tenderness, pain, and Doppler activity in patients with RA. Methods: A total of 110 hand joints (1 wrist, 5 MCPs & PIPs bilaterally) in 5 female patients with RA who did not respond to antirheumatic treatment were clinically examined with patient-reported outcomes (PROs) for joint swelling, tenderness, and pain (VAS). Using Kaltenborn's technique, the MCP2-5 joints in 1 randomized hand (4/5 patients, n=20) were manually mobilized. Synovitis, tenosynovitis and disease activity were evaluated using the ultrasound Doppler quantification method. Three treatment sessions, each with two segments, were carried out every 2nd day for 1 week. Results: Out of the 20 MCP joints treated in the test-hand, 75% (15/20) were self-reported as tender. Of these, 67% (10/15) were non-tender after the 3rd treatment session (1 week). In the control-hand, 60% (12/20) were self-reported as tender. Of these, 50% (6/12) were non-tender after 1 week. Both hands combined yielded highly significant reductions in self-reported tenderness (27/40 vs. 11/40, OR 5.48 [2.10, 14.28], p<0.001). After combining bilateral baseline tenderness with reduced bilateral tenderness after 1 week, patient and physician assessments of both hands demonstrated clinically relevant agreement (0.419, p=0.007). The VAS score (mean ± SD) for the test-hand at baseline was 60.0 (±22.1) vs. 40.0 (±24.2) after the last treatment session (p=0.003). The mean for the control hand was 50.4 (±25.0) at baseline vs. 31.0 (±23.9) after the last treatment session (p=0.036). There was a 14.2% overall reduction in quantitative Doppler activity from the treated joints at baseline (51.5±35.7) vs. all treatment segments within the 1st and 3rd treatment sessions over 1 week (37.3±31.6) (p<0.002). When comparing solely to the final segment of the 3rd treatment session, the treated joints had the largest mean decrease from baseline (21.0%, 51.5±35.7 vs. 30.5±30.8) (p<0.002) (figure ). Conclusions: An overall pattern of tenderness and pain reduction from baseline to post treatment and even among the control hand was observed, suggesting symmetry behind pain perception in RA. A strong patient-reported effect is present with pain outcomes and quantitative ultrasound helps with identifying changes in inflammation. A highly significant decrease in Doppler activity was observed. The remarkable ultrasound findings may indicate possible physiological microcirculatory changes as a result of joint mobilization therapy. These results support further studies of Kaltenborn's manual mobilization as a relatively safe, complementary treatment option for RA patients with tender hand joints despite antirheumatic therapy. Disclosure of Interest: A. Levitsky: None declared, Y. Kisten: None declared, P. Nordström: None declared, S. Lind: None declared, N. Vivar: None declared, R. van Vollenhoven Grant/research support from: AbbVie, BMS, GSK, Pfizer, Roche, UCB, Consultant for: AbbVie, Biotest, BMS, Crescendo, GSK, Janssen, Lilly, Merck, Pfizer, Roche, UCB, Vertex